General commentary: Is the moon there if nobody looks—Bell inequalities and physical reality - Gill, Richard D.; Lambare, Justo Pastor (Frontiers in Physics, 2022)
In a controversial paper recently published in this journal, Marian Kupczynski claims that Bell-CHSH inequalities cannot be derived for a classical probabilistic causal model of a typical Bell experiment. Such an experiment can be seen as built up of four separate components, one for each of the four different combinations of settings used in the experiment. In this "Comment" we show that his claim is false and his logical reasoning is incorrect.